Highlights from Faraday Discussion 182: Solid Oxide Electrolysis: Fuels and Feedstocks from Water and Air, York, UK, July 2015. Issue 9 (13th January 2016) - Stefan, Elena; Norby, Truls
Abstract : The rising importance of converting high peak electricity, from renewables to fuels has urged field specialists to organize this Faraday Discussion on Solid Oxide Electrolysis. Abstract : The rising importance of converting high peak electricity from renewables to fuels has urged field specialists to organize this Faraday Discussion on Solid Oxide Electrolysis. The topic is of essential interest in order to achieve a greater utilization of renewable energy and storage at higher densities.